2017
DOI: 10.1007/s11130-017-0629-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased Postharvest Life of TomLox B Silenced Mutants of Tomato (Solanum lycopersicum) Var. TA234

Abstract: A healthy lifestyle includes fruits and vegetables consumption. Tomato is one of the most consumed vegetables, although it is susceptible to physical damage through postharvest handling, thus leading to important losses. Softening is an important variable during tomato ripening; excessive softening is undesirable and leads to postharvest losses. TomloxB plays an important role in ripening, mainly in the loss of cellular integrity caused by fatty acids released from the lipid matrix of membranes that initiate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…1 ). In general, the highest activity was found in the pink stage, as reported by several authors ( 17 , 18 ). However, other authors found the highest activity at the red stage ( 1 , 8 ).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…1 ). In general, the highest activity was found in the pink stage, as reported by several authors ( 17 , 18 ). However, other authors found the highest activity at the red stage ( 1 , 8 ).…”
Section: Resultssupporting
confidence: 82%
“…The decreased LOX activity in the transgenic lines is very likely a direct consequence of the TomloxB gene silencing, as León-García et al . ( 17 ) proved.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations